2022
DOI: 10.3390/molecules27134303
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of Traditional Chinese Medicine Natural Compounds as Potential Myostatin Inhibitors: An In Silico Approach

Abstract: Myostatin (MSTN), a negative regulator of muscle mass, is reported to be increased in conditions linked with muscle atrophy, sarcopenia, and other muscle-related diseases. Most pharmacologic approaches that treat muscle disorders are ineffective, emphasizing the emergence of MSTN inhibition. In this study, we used computational screening to uncover natural small bioactive inhibitors from the Traditional Chinese Medicine database (~38,000 compounds) for the MSTN protein. Potential ligands were screened, based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…4 . Due to our interests in myogenesis, we explored the roles played by MSC activation, regeneration [ 10 ], extracellular matrix protein production [ 10 ], and natural compounds [ 20 , 21 , 32 ] in SM aging and related diseases. Our laboratory is devoted to the screening of natural compounds and designing peptides against selected targets responsible for SM degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…4 . Due to our interests in myogenesis, we explored the roles played by MSC activation, regeneration [ 10 ], extracellular matrix protein production [ 10 ], and natural compounds [ 20 , 21 , 32 ] in SM aging and related diseases. Our laboratory is devoted to the screening of natural compounds and designing peptides against selected targets responsible for SM degeneration.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, MSTN is a key therapeutic target. 25 ZINC85592908, according to Ali et al, 26 may prevent downstream signaling by blocking the MSTN protein and increasing myogenesis in skeletal muscle tissues. ZINC85592908 also has anti-MSTN protein therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture experiments have also revealed that MSTN inhibits the proliferation and differentiation of cultured muscle cell lines and primary myogenic cells [93], which suggests siRNA1 and siRNA5 might reduce MSTN gene expression and boost sheep meat yield [94]. Some natural compounds [95][96][97] and inhibitory peptides targeting MSTN [21,98], such as Ac-MIF1 and Ac-MIF2-NH2, have been reported to inhibit the effect of MSTN significantly and enhance cell proliferation [99]. Additionally, in vivo and in vitro data showed that FMOD prevents muscle aging by decreasing the activity of MSTN protein [92].…”
Section: Myostatinmentioning
confidence: 99%